2020
DOI: 10.3390/w12113245
|View full text |Cite
|
Sign up to set email alerts
|

Implications of Nutrient Enrichment and Related Environmental Impacts in the Pearl River Estuary, China: Characterizing the Seasonal Influence of Riverine Input

Abstract: The Pearl River estuary is an ecologically dynamic region located in southern China that experiences strong gradients in its biogeochemical properties. This study examined the seasonality of nutrient dynamics, identified related environmental responses, and evaluated how river discharge regulated nutrient sink and source. The field investigation showed significant differences of dissolved nutrients with seasons and three zones of the estuary regarding the estuarine characteristics. Spatially, nutrients exhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…These point sources of pollution were related to the dense urban agglomeration downstream of the Pearl River. In the Pearl River Delta region, the total amount of sewage ranged from 12,000 to 18,000 t/a in 2008-2017 [35], and the sewage discharge was the first contributor to TP in the Pearl River [36].…”
Section: Resultsmentioning
confidence: 99%
“…These point sources of pollution were related to the dense urban agglomeration downstream of the Pearl River. In the Pearl River Delta region, the total amount of sewage ranged from 12,000 to 18,000 t/a in 2008-2017 [35], and the sewage discharge was the first contributor to TP in the Pearl River [36].…”
Section: Resultsmentioning
confidence: 99%
“…Continuous freshwater discharge during the rainy season (generally April to October in the Lingdingyang Estuary) plays an important role in facilitating the cross‐boundary transportation of nutrients between terrestrial and marine environments (Niu et al., 2020; M. Wu et al., 2016; Ye et al., 2018). Nitrogen from allochthonous sources transported during these “hot moments” has the potential to significantly subsidize ecosystem metabolism (Z. Lu et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Spatially, nitrogen and phosphorus pollution trends are more prominent in the east but inconspicuous in the west. Dissolved inorganic nitrogen (DIN) in the PRE indicated that upstream of the mouth is dominated by NH 4 -N, and the concentration of NO 3 -N was the highest at the mouth, accounting for 51.2%-80.4% (Niu et al, 2020b;Li et al, 2022). Generally, the level of nitrogen and phosphorus nutrients is one of the key drivers of red tides in the PRE.…”
Section: Nutrientsmentioning
confidence: 99%
“…The vertical exchange of nutrients is hindered, limiting the growth of phytoplankton in the PRE. Niu et al (2020b) showed that the annual average sediment load in the PRE was mainly carried by runoff during 1974-2016. Moreover, they found that a large amount of suspended matter affected the growth of phytoplankton by influencing their photosynthesis.…”
Section: Hydrodynamic Forcesmentioning
confidence: 99%